Contestation over an island imaginary landscape: The management and maintenance of touristic nature. (May 2017) - Kothari, Uma; Arnall, Alex
This article demonstrates how maintaining high-end tourism in luxury resorts requires recreating a tourist imaginary of pristine, isolated and unpeopled island landscapes, thus necessitating the ceaseless manipulation and management of space. This runs contrary to the belief that tourism industries are exerting an increasingly benign influence on local environments following the emergence of 'sustainable tourism' in recent decades. Rather than preventing further destruction of the 'natural' world, or fostering the reproduction of 'natural' processes, this article argues that the tourist sector actively seeks to alter and manage local environments so as to ensure their continuing attractiveness to the high-paying tourists that seek out idyllic destinations. Additionally, by drawing on an example of tourism development, environmental change and local conflict in the Maldives, it shows how interventions by tourism managers can result in conflict with local people who, possessing different imaginaries, interests and priorities, may have their own, often long-established, uses of the environment undermined in the process. The article concludes that the growing diversity and increasing environmental awareness of tourists is currently producing a range of complexities and ambiguities that preclude any easy and straightforward environmental response by the sector, and ultimately might destabilise the Western-based tourist imaginary itself.